Specific Histologic Type of Leiomyoma Related to Estrogen Receptor Expression - I Gde Sastra Winata; Ni Wayan Armerinayanti; Desak Putu Oki Lestari (Warmadewa University, 2022)
Uterine Leiomyoma or fibroid is the most common gynecologic benign neoplasm which arising from monoclonal proliferation of smooth muscle cells in uterine wall. Some specific types of uterine leiomyoma, such ascellular leiomyoma, symplastic leiomyoma, mitotically active leiomyoma andmyxoid leiomyomahave different histomorphology from usual type leiomyoma. It also have wide variety of tumors size, but this study found that no correlation between type of leiomyoma and its size. Additional non-invasive therapy that predominantly developed in leiomyoma include many antagonist agents of estrogenic receptor. So, important to determine of estrogen receptor activity before that hormonal therapy prescription.Histopathology parameter that predict estrogen receptor activity in leiomyoma was not well understood. This study also try to correlate between specific histologic type of leiomyoma and estrogen receptor activity. This study was a retrospective crossectional study which analized by pearson chi-square test with p value < 0.05 and CI 95%. Result: There was significant correlation between specific histologic type of leiomyoma and estrogen receptor expression (p=0.007; p<0.05). Key Words: Leiomyoma, Estrogen Receptor